A formação pré e em serviço do professor de inglês do ensino fundamental I - Padre, Brenda Treco (2019)
With the social and ideological changes which recognize and stimulate the teaching of English language in Brazil, there is a big and increasing number of Brazilian schools inserting English in the initial grades of Brazilian Elementary School I. Despite the demand, there are still no official parameters to guide the teaching of additional languages in this segment. For this reason, this study had as its main objective a critical investigation of the private and public Brazilian Elementary School I English teachers’ pre and in-service education, through the Brazilian Law of Directives and Bases of National Education and the Brazilian National Common Curricular Base, along with courses syllabi, a questionnaire and interviews given to teachers. More specifically, this study aimed to 1. analyze, in the light of the dialogic senses effects and the senses and meanings, the discourses built in and on the studied context, materialized in the official documents, in the courses syllabi, in the questionnaires, and interviews; 2. identify the pre and in-service education inserted in the discourses, and 3. interpret the problematic of this focal human activity sphere. The data collection was carried through the gathering and production of 2 official documents, 6 courses’ syllabi, as well as the application of a questionnaire to 45 teachers and an interview given to 4 of them. Through the gathering and production of the data, the study concluded that there is an incoherence, since 1. the official documents seem to orient the education of teachers, but 2. the official syllabi don’t report how they educate their teachers, and 3. the discourses point out teachers who have theoretical and practical knowledge. Therefore, it is possible to identify that the participants in this study resort to the in-service courses, which orient their practices and educate them for the teaching of English to children. Finally, reflections on the education of English teachers in the context of Brazilian Elementary School I were proposed, with the objective of exposing and suggesting potential ways of rethinking the pre and in-service education of the professionals working in the area